Weaving healthy behaviors into new technology routines: Designing in (and for) the COVID-19 work-from-home period - Ren, Xipei; An, Pengcheng; Bekker, Tilde; Chen, Yu; Khot, Rohit Ashok; ten Bhömer, Martijn; Wang, Yunlong; Spina, Gabriele (2020)
Sitting in front of computers has become a major part of our workaday routines, challenging us in maintaining active and healthy lifestyles. This challenge becomes even more salient during this worldwide work-from-home period due to COVID-19. While a wide variety of existing interactive systems have been developed to facilitate health tracking and healthy exercises, relatively little research concerns incorporating healthy behaviors as HCI elements. To maximize pervasive health benefits in users’ technology routines, this workshop sets out to explore a design paradigm that enables users to use lightweight, healthy behaviors to perform daily interactions with computing systems. To navigate this new design space, this workshop calls for interdisciplinary endeavors, synergizing expertise from HCI design, health informatics, persuasive technology, exertion game, and psychology.